“In the Beginning”: Initiation of Minus Strand DNA Synthesis in Retroviruses and LTR-Containing Retrotransposons - Le Grice, Stuart F. J (Biochemistry (Easton), 2003)
Sequestering a host-coded tRNA for initiation of minus (−) strand DNA synthesis is central to the reverse transcription cycle of a number of retroviruses and long terminal repeat (LTR) retrotransposons. However, “self-priming” from a hydrolysis product of the viral genome has been observed for the LTR retrotransposon Tf1 and most likely exists for related elements. Furthermore, in contrast to retroviruses, where DNA synthesis is initiated from the 3‘-terminus of the cognate tRNA primer, examples are available where nucleotides of the tRNA anticodon domain are complementary to the viral primer binding site (PBS), necessitating internal cleavage of the primer to provide the appropriate 3‘-OH for DNA synthesis. Thus, although the ensuing steps of reverse transcription are common to these elements, several variations in which the replication primer is used have been exploited. In addition, the PBS of the viral RNA genome can vary in size from an 11 nt sequence, through a bipartite cis-acting element, to 18 contiguous nucleotides complementary to the 3‘-end of the replication primer. These diverse tRNA−viral RNA interactions, and their consequences for initiation of (−) strand DNA synthesis, are the subject of this review.